Jesus and Other Men Ideal Masculinities in the Synoptic Gospels - Asikainen, Susanna (Biblical Interpretation Series, 2018)
In Jesus and Other Men, Susanna Asikainen explores the masculinities of Jesus and other male characters and the ideal femininities in the Synoptic Gospels. Readership: Anyone interested in masculinities and gender in the New Testament and in the ancient Greco-Roman world